Etiology of Symptomatic Focal Epilepsy based on Neuroimaging Result in Neurology Outpatient Clinic of Dr. Hasan Sadikin General Hospital - Agastya Prabhaswara; Suryani Gunadharma; Uni Gamayani (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Focal epilepsy is the most common type of epilepsy that can be caused by structural lesions. Images from neuroimaging can show those structural lesions that may point to the etiology of epilepsy and would affect the management of epilepsy. The aim of the study was to explore the possible etiology of symptomatic focal epilepsy from neuroimaging result at the Neurology Outpatient Clinic in Dr. Hasan Sadikin General Hospital.Methods: This study was a cross-sectional descriptive study. The medical records that fulfilled the inclusion criteria were collected at the Neurology Outpatient Clinic of Dr. Hasan Sadikin General Hospital from the year 2017. The inclusion criteria were symptomatic focal epilepsy patients that had abnormal neuroimaging result.Results: In total, there were 71 medical records collected of which eight etiologies of symptomatic focal epilepsy were found, that were vascular disorder caused by strokes (33%), tumors (21%), hippocampal sclerosis (20%), infections (11%), head trauma (6%), malformations of cortical development (4%), vascular malformations (3%), and phakomatosis (1%). Vascular disorder was the most abundant etiology found in all brain lobes, except in temporal and frontal lobes, which also most often caused by hippocampal sclerosis and tumors, respectively.Conclusions: Vascular disorders due to stroke, is the most abundant etiology found in symptomatic focal epilepsy, therefore, stroke patients need to be informed about the possibility of having epilepsy later on.